2023
DOI: 10.3390/math11183977
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Cavitating Jet Flow Field with Different Turbulence Models

Lidong Li,
Yan Xu,
Mingming Ge
et al.

Abstract: In numerous industries such as drilling, peening, cleaning, etc., a cavitating jet is adopted. However, it is challenging to simulate the cavitating flow field numerically with accuracy. The flow field of the organ pipe cavitation nozzle is simulated in this research using the RNG k−ε, DES, and LES turbulence models. The LES model can more accurately predict the periodic shedding of a cavitating cloud, which is basically consistent with the jet morphology captured with a high−speed camera. The flow pattern, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Their results showed that most turbulence models do not adequately simulate turbulence-related aspects such as Reynolds stress and turbulent kinetic energy. Li et al [10] studied the flow field of an organ pipe cavitation nozzle using RNG k − ϵ, DES, and LES turbulence models, finding that the LES model most accurately predicts the periodic shedding of cavitating clouds, closely matching high-speed photographic observations. The LES model excels in simulating the dynamic behaviors and vortex structures within the nozzle, providing a superior depiction of cavitation phenomena compared to the RNG k − ϵ and DES models, and offering valuable insights for the further simulation and analysis of cavitating jets.…”
Section: Introductionmentioning
confidence: 89%
“…Their results showed that most turbulence models do not adequately simulate turbulence-related aspects such as Reynolds stress and turbulent kinetic energy. Li et al [10] studied the flow field of an organ pipe cavitation nozzle using RNG k − ϵ, DES, and LES turbulence models, finding that the LES model most accurately predicts the periodic shedding of cavitating clouds, closely matching high-speed photographic observations. The LES model excels in simulating the dynamic behaviors and vortex structures within the nozzle, providing a superior depiction of cavitation phenomena compared to the RNG k − ϵ and DES models, and offering valuable insights for the further simulation and analysis of cavitating jets.…”
Section: Introductionmentioning
confidence: 89%
“…The simulation nozzle model was consistent with the experimental nozzle. The computational boundary must be kept a long way from the nozzle exit in order to reduce its impact on the core area of the jet [26]. Fluent software was thus used to generate a twodimensional axisymmetric flow field calculation domain with a length of 100 mm and a width of approximately 30 mm (see Figure 3); it is believed that the model boundary has no effect on the core area of the jet.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…With sufficient computational resources, more information on turbulence can be obtained. The method has been extensively used to study nozzle cavitation [20][21][22][23]. Kim et al [24] used LES to investigate the influences of initial momentum thickness on free jet flow in a circular hole, discovering that these factors have a significant impact on the free jet's flow characteristics.…”
Section: Introductionmentioning
confidence: 99%